Clinicopathological Features of Bone Marrow Infiltration in Hodgkin Lymphoma. Should Bone Marrow Staging Be Done Only in High Risk Patients? - Muthu SUDALAIMUTHU; Debdatta BASU2 (Federation of Turkish Pathology Societies, 2017)
Objective: The frequency of bone marrow infiltration by Hodgkin lymphoma is low and varies from 3 to 18%. Hence there exists a dilemma whether bone marrow staging should be done only in the high risk cases. This study aims to study the clinicopathological features and the histomorphology of bone marrow infiltration by Hodgkin Lymphoma. Material and Method: Bone marrow aspirates and biopsies from cases of Hodgkin lymphoma diagnosed between 2007 and 2015 were studied. Immunohistochemistry with CD15 and CD30 were done in necessary cases. Bone marrow infiltration was correlated with various clinicopathological parameters. Results: Ten of the 81 cases (12.3%) studied showed infiltration by Hodgkin lymphoma in the bone marrow biopsy sections. All the aspirates were negative. Bone marrow in the involved cases showed Reed-Sternberg cells and/or mononuclear Hodgkin cells positive for CD30 in a polymorphous inflammatory background. Cases of lymphocyte depleted subtype (66%) and those with leucopenia/ thrombocytopenia (100%) were frequently associated with bone marrow infiltration. B-symptoms, anemia and mixed cellularity were the other risk factors. However none of these risk factors were noted in two out of the ten cases with bone marrow infiltration. Conclusion: As the role of bone marrow aspirate is minimal in the staging of Hodgkin lymphoma, bone marrow biopsy should be the method of choice. Immunohistochemistry helps in the doubtful cases. Bone marrow involvement was frequent but not confined to the high risk groups. Our findings suggest that bone marrow staging should not be restricted to the high risk cases alone.